Role of vertical farming for sustainable urban horticulture: A review - Jemal Seid Hussen; Gebeyaw E. Ahmed (Advances in Horticultural Science)
New constraints such as urbanization, food security, farmland scarcity, and escalating greenhouse gas emissions underscore the importance of vertical farming. This eco-friendly method offers a promising solution to traditional farming, aiding a growing global populace in securing sustenance. Resource use efficiency of vertical farming and the ability to produce premium agricultural goods are driving its global appeal. Particularly beneficial in areas with limited soil and water resources, vertical farming could play a vital role in sustaining fruit and vegetable production. Vertical agriculture emphasizes the critical need for urban centers to combat pollution and escalating food expenses by prioritizing self-reliance through local food production. Advanced cultivation techniques like hydroponics and aeroponics make vertical farming viable for urban environments, requiring minimal oversight and yielding higher outputs. Despite its potential, vertical farming encounters obstacles such as steep upfront and operational costs, complexity, and maintenance demands for optimal growth conditions. To promote urban agriculture, there is a need for enhanced extension services to educate and train growers and farmers on vertical farming techniques for producing diverse horticultural yields.